Civil Society in Muslim Contexts: The Problématique and a Critique of Euro-American Perspectives - Anjum, Tanvir (Islamic Studies, 2012)
Insisting on the historical and cultural specificity of the concept of civil society, many European and American scholars argue that it is a unique product of Europe, and its application to non-European contexts, particularly to the Muslim societies, is impossible or at least problematic, since the necessary pre-conditions for the existence of civil society are largely missing in them. In response, these dogmatic assertions have been challenged by proving theoretical possibility of existence of the civil society in Muslim contexts as well as by bringing empirical evidence to the fore. The present study is an attempt to analyze the assertions about the incompatibility of Islam with civil society. It highlights the limitations of the Euro-American perspectives on this issue, examines the contested role of religion in civil society, and locates the varied expressions of civil society in Muslim societies.